Post‐Stocking Annual Survival of Fingerling‐ and Catchable‐Sized MYY Brook Trout Salvelinus fontinalis in a Small Stream - Jennifer L. Vincent; Kevin A. Meyer (Aquaculture, Fish and Fisheries, 2025)
Abstract The use of hatchery male fish with two Y chromosomes (MYY) to progressively shift sex ratios of wild populations to 100% male is a novel approach for eradication of undesirable nonnative fish populations, but MYY fish must survive post‐release to successfully reproduce. Post‐release apparent survival of 250 mm MYY brook trout Salvelinus fontinalis stocked in a small stream averaged % annually over the first five years of stocking but increased to 17% once stocking size was reduced to 130 mm. Results suggest that successful MYY eradication programmes may be contingent in part on MYY stocking size.